Cystatin C and incident peripheral arterial disease events in the elderly: results from the Cardiovascular Health Study. - O'Hare, Ann M; Newman, Anne B; Katz, Ronit; Fried, Linda F; Stehman-Breen, Catherine O; Seliger, Stephen L; Siscovick, David S; Shlipak, Michael G (Arch Intern Med, 2005)
BACKGROUND: The association of cystatin C, a novel marker of renal function, with risk for developing complications related to peripheral arterial disease (PAD) has not been examined. METHODS: We evaluated the hypothesis that a high cystatin C concentration is independently associated with future PAD events among 4025 participants in the Cardiovascular Health Study who underwent serum cystatin C measurement at the 1992-1993 visit and who did not have PAD at baseline. The association of cystatin C quintiles with time to first lower-extremity PAD procedure (bypass surgery, angioplasty, or amputation) was evaluated using multivariable proportional hazards models. Secondary analyses were conducted using quintiles of serum creatinine level and estimated glomerular filtration rate (eGFR). RESULTS: The annualized risk of undergoing a procedure for PAD was 0.43% per year among participants in the highest cystatin C quintile (>1.27 mg/L) compared with 0.21% per year or less in all other quintiles. After multivariable adjustment for known risk factors for PAD, elevated cystatin C levels remained associated with the outcome (hazard ratio, 2.5 for highest vs lowest quintile of cystatin C, 95% confidence interval, 1.2-5.1). The highest quintiles of serum creatinine level and eGFR were not associated with future PAD events in either unadjusted or adjusted analyses. CONCLUSION: Elevated concentrations of cystatin C were independently predictive of incident PAD events among community-dwelling elderly patients.
Keywords: Aged; Cohort Studies; Cystatin C; Cystatins; Female; Health Surveys; Humans; Longitudinal Studies; Male; Peripheral Vascular Diseases; Predictive Value of Tests; Risk Factors; ROC Curve; United States

Mortality and cardiovascular risk across the ankle-arm index spectrum: results from the Cardiovascular Health Study. - O'Hare, Ann M; Katz, Ronit; Shlipak, Michael G; Cushman, Mary; Newman, Anne B (Circulation, 2006)
BACKGROUND: A low ankle-arm index (AAI) is a strong predictor of mortality and cardiovascular events. A high AAI also appears to be associated with higher mortality risk in select populations. However, mortality and cardiovascular risk across the AAI spectrum have not been described in a more broadly defined population. METHODS AND RESULTS: We examined total and cardiovascular mortality and cardiovascular events across the AAI spectrum among 5748 participants in the Cardiovascular Health Study (CHS). The mean age of the sample population was 73+/-6 years, and the sample included 3289 women (57%) and 883 blacks (15%). The median duration of follow-up was 11.1 (0.1 to 12) years for mortality and 9.6 (0.1 to 12.1) years for cardiovascular events. There were 2311 deaths (953 of which were cardiovascular) and 1491 cardiovascular events during follow-up. After adjustment for potential confounders, AAI measurements < or =0.60 (hazard ratio [HR] 1.82, 95% CI 1.42 to 2.32), 0.61 to 0.7 (HR 2.08, 95% CI 1.61 to 2.69), 0.71 to 0.8 (HR 1.80, 95% CI 1.44 to 2.26), 0.81 to 0.9 (HR 1.73 95% CI 1.43 to 2.11), 0.91 to 1.0 (HR 1.40, 95% CI 1.20 to 1.63), and >1.40 (HR 1.57, 95% CI 1.07 to 2.31) were associated with higher mortality risk from all causes compared with the referent group (AAI 1.11 to 1.20). The pattern was similar for cardiovascular mortality. For cardiovascular events, risk was higher at all AAI levels <1 but not for AAI levels >1.4 (HR 1.00, 95% CI 0.57 to 1.74). The association of a high AAI with mortality was stronger in men than in women and in younger than in older cohort members. CONCLUSIONS: In a cohort of community-dwelling elders, mortality risk was higher than the referent category of 1.11 to 1.2 among participants with AAI values above the traditional cutpoint of 0.9 (ie, 0.91 to 1.0 and >1.4), and the specific association of AAI with mortality varied by age and gender.
Keywords: Aged; Ankle; Arm; Blood Pressure; Body Mass Index; Cholesterol, LDL; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Peripheral Vascular Diseases; Risk Factors; Smoking

Patterns and predictors of recovery from exhaustion in older adults: the cardiovascular health study. - Whitson, Heather E; Thielke, Stephen; Diehr, Paula; O'Hare, Ann M; Chaves, Paulo H M; Zakai, Neil A; Arnold, Alice; Chaudhry, Sarwat; Ives, Diane; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To estimate the likelihood of, and factors associated with, recovery from exhaustion in older adults. DESIGN: Secondary analysis of a cohort study. SETTING: Six annual examinations in four U.S. communities. PARTICIPANTS: Four thousand five hundred eighty-four men and women aged 69 and older. MEASUREMENTS: Exhaustion was considered present when a participant responded "a moderate amount" or "most of the time" to either of two questions: "How often have you had a hard time getting going?" and "How often does everything seem an effort?" RESULTS: Of the 964 participants who originally reported exhaustion, 634 (65.8%) were exhaustion free at least once during follow-up. When data from all time points were considered, 48% of those who reported exhaustion were exhaustion free the following year. After adjustment for age, sex, race, education, and marital status, 1-year recovery was less likely in individuals with worse self-rated health and in those who were taking six or more medications or were obese, depressed, or had musculoskeletal pain or history of stroke. In proportional hazards models, the following risk factors were associated with more persistent exhaustion over 5 years: poor self-rated health, six or more medications, obesity, and depression. Recovery was not less likely in participants with a history of cancer or heart disease. CONCLUSION: Exhaustion is common in old age but is dynamic, even in those with a history of cancer and congestive heart failure. Recovery is especially likely in seniors who have a positive perception of their overall health, take few medications, and are not obese or depressed. These findings support the notion that resiliency is associated with physical and psychological well-being.
Keywords: Aged; Aging; Cardiovascular Physiological Phenomena; Exercise Test; Exercise Tolerance; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Predictive Value of Tests; Recovery of Function; Retrospective Studies; United States